Antinociceptive, anti-inflammatory effects and safety of Ziziphus mistol fruits - Reynoso, Marcos Adrian (2016)
Ziziphus mistol Griseb. (Rhamnaceae), popularly known as ?mistol,? is widely distributed throughout Perú, Bolivia, Paraguay and Argentina. Its fruit is consumed in different forms in several argentinean communities. The present study was carried out to investigate the medicinal properties and safety of Ziziphus mistol (mistol) fruits ethanol and aqueous extracts and arrope. Antinociceptive activity was assessed using the formalin, acetic acid-induced writhing and tail-ﬂick tests in rats. Anti-inﬂammatory effects were determinated through carrageenan induced edema test and cotton pellet-induced granuloma formation, in rats. The safety was evaluated with test of acute toxicity (48 hs) and sub-chronic toxicity (91 days).All extracts (1,000 mg / kg body weight) showed significant inhibition (P <0.05) in the pain and inflammation experimentally induced. In the acute toxicity study, a single dose of 4000 and 8000 mg/kg b.w., produced no mortality and no clinical signs of disease were observed after 48 h. In the sub-chronic toxicity study the extracts no caused significant visible signs of toxicity, nor mortality for 91 consecutive days of treatment. No significant differences were found in relative organ weights and hematological and biochemical parameters between the treated groups and the control groups. Aqueous extract and arrope of Z. mistol fruits could be good source of antinociceptive and anti-inflamatory agents because of its good activity and safety.